Mixed valency in a neutral 1D Fe-chloranilate coordination polymer. Issue 24 (7th June 2022) - Clutterbuck, Katelyn M.; Abrahams, Brendan F.; Hudson, Timothy A.; van Koeverden, Martin P.
Abstract : A neutral Fe-chloranilate chain, with triphenylphosphine oxide co-ligands, represents a rare example of a one-dimensional chain in which there is a temperature dependent electron transfer from the Fe(ii ) centre to the bridging chloranilate ligand. Abstract : The syntheses and structures of a pair of neutral one-dimensional (1D) Fe-anilate based coordination polymers, Fe(Fan)(4, 4′-bipy)2 (Fan n − = deprotonated 3, 6-difluoro-2, 5-dihydroxy-1, 4-benzoquinone; 4, 4′-bipy = 4, 4′-bipyridine) and Fe(Clan)(OPPh3 )2 (Clan n − = deprotonated 3, 6-dichloro-2, 5-dihydroxy-1, 4-benzoquinone; OPPh3 = triphenylphosphine oxide), are reported. In the case of Fe(Fan)(4, 4′-bipy)2, the Fe centre is in the +2 oxidation state and the Fan ligand is present in its quinoidal, dianionic form. In contrast, the structurally similar Fe(Clan)(OPPh3 )2 chain contains Fe centres and chloranilate ligands in oxidation states close to +3 and −3 respectively at low temperature. It is suggested that intrachain π–π interactions aid electron transfer from the Fe centres to the bridging ligands.